Analysis of Occupational Safety and Health (K3) Competency of Outsourced Workers on Employee Performance: Implications for Occupational Accident Risk Control (Survey Study at PT PLN Nusantara Power Unit Generation in Central Kalimantan) - Kurniawan, Anang; Paramarta, H. Vip; Mulyani, Sri Rochani (Dinasti Publisher, 2026)
This study aims to analyze the influence of Occupational Health and Safety (OHS) competence of outsourced workers on employee performance and its implications for occupational accident risk control. A quantitative approach was employed using a survey method conducted among outsourced workers at PT PLN Nusantara Power, Pulang Pisau Generation Unit. Questionnaires were used to gather data, which was then analysed using the SPSS technique. The results indicate that OHS competence has a significant positive effect on employee performance, and employee performance directly influences the effectiveness of occupational accident risk control. This research highlights the vital role of outsourced workers in supporting company operations, particularly in the electricity generation sector, which is characterized by a high-risk work environment. The findings contribute to emphasizing the importance of systematically and continuously improving OHS competence to enhance employee performance and create a safe and productive work environment. The novelty of this study lies in its specific examination of outsourced workers’ OHS competence as both a direct and indirect predictor of employee performance and occupational accident risk control within a high-risk electricity generation context.